EOP determination using VLBI at IGN ARGENTINA - Cañas, N. L. (2025)
Very Long Baseline Interferometry (VLBI) is an important technique in Space Geodesy, making innovative use of radio telescopes to observe distant quasars that emit strong radio waves. The signals received at multiple antennas are recorded and compared to determine time delays, which, combined with geometric models, allow precise calculation of the baseline between them. Multiple observations improve the accuracy of antenna positions and enable real-time determination of Earth Orientation Parameters (EOP). With the establishment of the Argentine-German Geodetic Observatory (AGGO), Argentina has acquired the infrastructure to contribute to the global VLBI network. In this context, the Center for Research in Applied Geodesy (GIGA) of the National Geographic Institute (IGN) incorporated VLBI into its core geodetic activities. Since April 2020, IGN has served as an associated analysis center of the International VLBI Service for Geodesy and Astrometry (IVS). It delivers daily SINEX files containing 24-hour EOP estimates and station coordinates. These contributions adhere to international standards for integration into IVS combinations and are produced using the scientific software VieVS, developed by the University of Vienna. In this presentation, we provide a comparative analysis of our EOP estimates with respect to those from other recognized IVS Analysis Centers and the International Earth Rotation and Reference Systems Service (IERS). The comparison includes daily solutions from 2014 onward, and global solutions based on this extended time series. The main objective of this analysis is to perform quality control on our products and to validate the accuracy and consistency of our results.